Experimental investigation of the effect of longitudinal tensile reinforcement ratio on ductility behaviour in GPC beams - Ahmet Şener; Mehmet Cemal Acar; Ali İhsan Çelik; Ahmet Özbayrak (Journal of Sustainable Construction Materials and Technologies)
This research first determined the strength of the cylindrical geopolymer concrete materi- als under compressive stresses. Secondly, conventional and geopolymer-reinforced concrete beams were manufactured in different reinforcement ratios, and their mechanical properties were compared under bending. The main aim of this study is to experimentally compare the effect of reinforcement ratio on the ductility behavior of an alkali-activated geopolymer con- crete (GPC) beam with that of an ordinary Portland cement (OPC) beam. First, balanced reinforcement calculations were made considering the mechanical properties obtained from the material tests. The load-displacement, moment-curvature, and crack development results obtained from beam tests are interpreted with this information. OPC and GPC beams exhibit- ed similar strength and crack development behavior. However, the behavior of GPC and OPC concretes differs regarding the ductility index. Therefore, to achieve similar ductility in the conduct of GPC and OPC beams, the balanced reinforcement ratio and section dimensions of GPC beams should be chosen to be larger than OPC.